Dedifferentiated leiomyosarcoma of the uterus: a clinicopathologic and immunohistochemical analysis of 23 cases. Issue 6 (8th February 2023) - Chapel, David B; Maccio, Livia; Bragantini, Emma; Zannoni, Gian F; Quade, Bradley J; Parra‐Herran, Carlos; Nucci, Marisa R
Abstract : Aims: To morphologically and immunophenotypically characterize dedifferentiated uterine leiomyosarcoma (LMS). Methods and results: We identified 23 dedifferentiated uterine LMS, defined as a malignant uterine smooth muscle tumour containing discrete differentiated and dedifferentiated components (i.e. with and without morphologic and immunophenotypic evidence of smooth muscle differentiation, respectively). The differentiated component was leiomyosarcoma in most cases (17/23), though some arose from a leiomyoma ( n = 4) or smooth muscle tumour of uncertain malignant potential ( n = 2). The dedifferentiated tumour component showed noncohesive polygonal cells with moderate to abundant cytoplasm, pleomorphic nuclei with coarse vesicular to smudged chromatin, one or more macronucleoli, frequent multinucleation, and atypical mitoses. Three cases showed heterologous osteosarcomatous or chondrosarcomatous differentiation. Immunohistochemistry revealed alterations characteristic of uterine LMS, including Rb loss (18/19); strong diffuse p16 (17/19); strong diffuse (9/19) or complete absence of (5/19) p53; and ATRX loss (6/16). Compared to a control cohort of uterine LMS without dedifferentiation, dedifferentiated uterine LMS showed significantly shorter disease‐specific (median, 54 versus 20 months; 5‐year DSS, 46% versus 36%; P = 0.04) and disease‐free (median, 31 versus 8 months; 5‐year DFS, 42% versus 8%; P = 0.002) survival. Of 19 dedifferentiated uterine LMS with follow‐up, 12 had died of disease at median 14 (range, 2–73) months; four were alive with disease at 4, 12, 44, and 50 months; and three were alive with no evidence of disease at 56, 109, and 114 months. Conclusion: Routine prospective recognition of dedifferentiated uterine LMS and distinction from mimics is advocated for accurate prognostication and for further characterisation of these tumours. Abstract : Approximately 2–5% of uterine leiomyosarcomas show dedifferentiation, characterised by a discrete tumour component without morphologic or immunophenotypic evidence of smooth muscle differentiation. Disease‐specific and disease‐free survival are significantly shorter for dedifferentiated than for nondedifferentiated uterine leiomyosarcoma, warranting prospective recognition. The molecular basis for dedifferentiation in uterine leiomyosarcoma remains uncertain.